Why do poverty reductions strategies in Northern Mountain, Vietnam not bring real results? - Nguyen Mau Dung; Lebailly, Philippe; Mai Lan Phuong (2012)
Poverty alleviation programs have been implemented in developing countries since the 1980s and 1990s, and will be continued into the next decades. The question is why "poverty issues" still exist and challenge not only the Vietnamese government but also many countries all over the world. One may ask if poverty reduction strategies, applied in Vietnam and other countries, are appropriate to the real poverty situation, and if they are sustainable.
This paper is based on research to investigate the nature of government's interventions as a "poverty reduction strategy," at Tu Ly and Xuan Phong communes in Hoa Binh province. Vietnam's official poverty identification method and participatory poverty assessment of people are applied. This study claims that the currently "inappropriate definition of poverty" is a key reason for the lack of success of the current poverty alleviation programs.
Keywords: Poverty reduction -- Government policy; Poverty reduction; Poverty; Poverty -- Developing countries